2004
DOI: 10.1016/j.chembiol.2004.03.028
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Natural Product Pironetin Selectively Targets Lys352 of α-Tubulin

Abstract: Pironetin is a potent inhibitor of tubulin assembly and arrests cell cycle progression in M phase. Analyses of its structure-activity relationships suggested that pironetin covalently binds tubulin. To determine the binding site of pironetin, we synthesized biotinylated pironetin, which inhibited tubulin assembly both in vitro and in situ. The biotinylated pironetin selectively and covalently bound with tubulin. Partial digestion of biotinylated pironetin-treated tubulin by several proteases revealed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
4
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 33 publications
3
68
4
1
Order By: Relevance
“…Because IEJLs possess a Michael addition-type reactive portion, the irreversibility of IEJLs might be owing to the covalent binding to target molecules like leptomycin B, pironetin, amphidinolide H, and so on. [22][23][24] However, since reducing reagent dithiothreitol, which inactivates the reactivity of most Michael addition-type inhibitors, did not interfere with V-ATPase inhibition by IEJLs (data not shown), covalent binding might not be necessary for V-ATPase inhibition as in the case of PP2A inhibitors fostriecin/ phoslactomycins. 25,26) Further investigation is required to clarify whether IEJLs covalently bind targets molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Because IEJLs possess a Michael addition-type reactive portion, the irreversibility of IEJLs might be owing to the covalent binding to target molecules like leptomycin B, pironetin, amphidinolide H, and so on. [22][23][24] However, since reducing reagent dithiothreitol, which inactivates the reactivity of most Michael addition-type inhibitors, did not interfere with V-ATPase inhibition by IEJLs (data not shown), covalent binding might not be necessary for V-ATPase inhibition as in the case of PP2A inhibitors fostriecin/ phoslactomycins. 25,26) Further investigation is required to clarify whether IEJLs covalently bind targets molecules.…”
Section: Discussionmentioning
confidence: 99%
“…2). To date, some bioactive compounds containing a,b-unsaturated lactone have been reported to bind to proteins by Michael addition, a reaction that is likely to be non-specific to biological nucleophiles such as cysteine residues; however, it has been shown that the binding of some compounds such as leptomycin B [28], and pironetin [6] to targeted proteins proceeds in a site and/or protein-specific manner. As for PP2A inhibitors, although it is speculated that fostriecin covalently binds to PP2Ac through the unsatulated lactone, the direct evidence has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several bioactive chemicals and their target proteins have been reported. One such example would be pironetin, which binds to Lys-352 of a-tubulin, inhibits tubulin assembly, and arrests cell cycle progression in M phase [6]. Another example reported to date is amphidinolide H, which binds to Tyr-200 of actin subdomain 4 and stimulates the formation of small actin-patches, followed by F-actin rearrangement into aggregates via the retraction of actin fibers [7].…”
Section: Introductionmentioning
confidence: 99%
“…Pironetin covalently binds to Lys352 of a-tubulin and inhibits the interaction of tubulin heterodimers (Usui et al, 2004). A JNK inhibitor, SP600125, was purchased from Tocris Cookson Inc. (Ellisville, MO, USA).…”
Section: Methodsmentioning
confidence: 99%